A three-dimensional Cu nanobelt cathode for highly efficient electrocatalytic nitrate reduction. Issue 17 (20th March 2020) - Wang, Xiaodan; Zhu, Mengqi; Zeng, Guoshen; Liu, Xun; Fang, Chihhsiang; Li, Chuanhao
Abstract : A three-dimensional Cu nanobelt cathode was developed to efficiently catalyze the electrocatalytic nitrate reduction process. Abstract : Water treatment techniques for destructive removal of nitrates by reducing them to harmless N2 have recently begun to emerge. In this study, we present a novel three-dimensional (3D) Cu nanobelt cathode for efficient electrochemical nitrate reduction. Upon an applied potential of −1.4 V vs. Ag/AgCl, the removal efficiency of nitrates by the 3D Cu nanobelt electrode reaches 100% at 60 min, compared to 2.6% for the Cu foam electrode under the same conditions. Based on the mass balance on nitrogen atoms, the major product is determined to be ammonia. In the simulated wastewater containing NaCl, the as-generated ammonia ions are simultaneously oxidized into harmless N2 by the in situ generated ClO − ions from the Pt anode, resulting in the complete removal of inorganic nitrogen (nitrate, nitride and ammonia) from wastewater. The mechanism for the improvement of electrocatalytic activity is systematically investigated. Firstly, the large surface area of the 3D Cu nanobelt electrode facilitates the mass transfer of nitrates, resulting in accelerated electrochemical kinetics. Secondly, linear sweep voltammetry (LSV) and electrochemical impedance spectroscopy (EIS) measurements confirm that the 3D Cu nanobelt electrode exhibits improved charge transfer ability. Also, further investigations demonstrate that the 3D Cu nanobelt electrode preferentially reacts with nitrates, compared to the pristine Cu foam electrode readily reacting with the dissolved oxygen (DO) to generate H2 O2 . This study might expand the prospects of electrocatalytic techniques towards the destructive removal of inorganic nitrogen pollutants in wastewater.